Penerapan Metode Qiro'ah Hikayah Untuk Meningkatkan Keterampilan Membaca Dalam Bahasa Arab Siswa Kelas XI di SMA 3 Negeri Palopo - Mutia, Mutia Ramadhani; Kartini; Mustafa (Universitas KH. Mukhtar Syafaat, 2025)
This research aims (1) to determine the implementation of the Qira’ah method in Arabic language learning for eleventh-grade students at SMA 3 Negeri Palopo, and (2) to identify efforts to improve Arabic language learning for eleventh-grade students at SMA 3 Negeri Palopo through the Qira’ah Hikayah method. The research procedure was conducted over two cycles, using Kurt Lewin's model, with each cycle consisting of four stages: planning, action, observation, and reflection. Each cycle comprised two meetings. The data collection methods used were action observation, tests, and field notes. The results of this study show that (1) the steps in implementing the Qira’ah Hikayah in this research are: 1. The researcher presents the material, 2. The researcher asks the students to repeat what has been read, 3. The researcher then asks the students to read the material one by one, 4. The researcher provides questions based on the material read, and 5. The researcher asks the students to submit their answers. The assessment results are calculated by dividing by two (50%). (2) The percentage in cycle I shows that out of 36 students, 3 students completed the tasks, resulting in a percentage of 8.33%, while 33 students did not complete the tasks, accounting for 91.6%. In cycle II, there was an improvement in student learning outcomes, with a percentage of 94.4%. Thus, the increase in student learning outcomes from cycle I to cycle II was 86.07%. Therefore, in cycle II, the students' reading skills improved, leading to a conclusion of completion